Heme oxygenase-1 (HO-1) cytoprotective pathway: A potential treatment strategy against coronavirus disease 2019 (COVID-19)-induced cytokine storm syndrome. (November 2020) - Rossi, Maxime; Piagnerelli, Michael; Van Meerhaeghe, Alain; Zouaoui Boudjeltia, Karim
Abstract: The outbreak of coronavirus disease 2019 (COVID-19) requires urgent need for effective treatment. Severe COVID-19 is characterized by a cytokine storm syndrome with subsequent multiple organ failure (MOF) and acute respiratory distress syndrome (ARDS), which may lead to intensive care unit and increased risk of death. While awaiting a vaccine, targeting COVID-19-induced cytokine storm syndrome appears currently as the efficient strategy to reduce the mortality of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The stress-responsive enzyme, heme oxygenase-1 (HO-1) is largely known to protect against inflammatory response in animal models. HO-1 is induced by hemin, a well-tolerated molecule, used for decades in the treatment of acute intermittent porphyria. Experimental studies showed that hemin-induced HO-1 mitigates cytokine storm and lung injury in mouse models of sepsis and renal ischemia-reperfusion injury. Furthermore, HO-1 may also control numerous viral infections by inhibiting virus replication. In this context, we suggest the hypothesis that HO-1 cytoprotective pathway might be a promising target to control SARS-CoV-2 infection and mitigate COVID-19-induced cytokine storm and subsequent ARDS.